Social Dominance Orientation Boosts Collective Action Among Low-Status Groups - Carvalho, Catarina L.; Pinto, Isabel R.; Costa-Lopes, Rui; Páez, Darío; Miranda, Mariana P.; Marques, José M. (Frontiers in Psychology, 2021)
We propose that low-status group members’ support for group-based hierarchy and inequality (i.e., social dominance orientation; SDO) may represent an ideological strategy to guarantee the legitimacy of future ingroup status-enhancement. Specifically, we argue that, under unstable social structure conditions, SDO serves as an ideological justification for collective action tendencies aimed at competing for a higher status. In such context, SDO should be positively related with actions aimed to favor the ingroup (i.e., collective actions) by increasing group members’ motivation to engage in direct competition with a relevant higher-status outgroup. We conducted two studies under highly competitive and unstable social structure contexts using real life groups. In Study 1 (N = 77), we induced Low vs. High Ingroup (University) Status and in Study 2 (N = 220) we used competing sports groups. Overall, results showed that, among members of low-status groups, SDO consistently increased individuals’ motivation to get involved in actions favoring the ingroup, by boosting their motivation to compete with the opposing high-status outgroup. We discuss the results in light of the social dominance and collective action framework.